2007
DOI: 10.1055/s-2007-981457
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Enzymatic Antioxidant Status in Patients with Hypothyroidism before and after Treatment

Abstract: The present study was designed to investigate the relationship between the serum levels of oxidant-antioxidant system (malondialdehyde (MDA) level, Paraoxonase (PON1) activity, nitric oxide (NO) level and superoxide dismutase (SOD) activity) and thyroid hormone status in hypothyroidism pre and posttreatment. The study group comprised 33 patients with primary hypothyroidism. 18 of these patients were reevaluated after euthyroid state i.e. at least 6 months of thyroxine replacement. The patients were compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
104
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(126 citation statements)
references
References 37 publications
11
104
1
3
Order By: Relevance
“…Only Baskol et al studied Hashimoto thyroiditis patients both before and after levothyroxine treatment and reported that MDA was higher in hypothyroid patients and still remained higher than the control groups even after being treated with levothyroxin. 20 Our findings on increased MDA, which is a marker for increased oxidative stress are in agreement with the results of Baskol et al 20 Turkiye Klinikleri J Med Sci 2012;32 (5) Mehmetçik ve ark.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Only Baskol et al studied Hashimoto thyroiditis patients both before and after levothyroxine treatment and reported that MDA was higher in hypothyroid patients and still remained higher than the control groups even after being treated with levothyroxin. 20 Our findings on increased MDA, which is a marker for increased oxidative stress are in agreement with the results of Baskol et al 20 Turkiye Klinikleri J Med Sci 2012;32 (5) Mehmetçik ve ark.…”
Section: Discussionsupporting
confidence: 91%
“…Only Baskol et al, Gerenova and Gadjeva reported on the differences in SOD levels both before and after levothyroxine treatment. 20,26 Although Gerenova and Gadjeva found an insignificant decrease in SOD levels in hypothyroid patients treated with levothyroxine, our results suggested significant decreases in the SOD levels. 26 On the contrary, Baskol et al found significant increases in SOD levels in Hashimoto thyroiditis patients treated with levothyroxine.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…The antioxidant enzyme activities were decreased, and then the superoxide radical and hydrogen peroxide intermediate radicals accumulate. These oxygen free-radicals could undergo the Fenton's reaction, generating hydroxyl radicals, which may lead to lipid peroxidation in cells [33]. Therefore, the reason of increased lipid peroxidation in camel-calves with pasteurellosis may be related to decreased antioxidant enzymes activity.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the components of several viruses (hepatitis C, human parvovirus B19, coxsackie and herpes viruses) were detected in the thyroid of Hashimoto's thyroiditis patients (Mori & Yoshida 2010). Moreover, the possible involvement of the oxidative stress profile in HT pathogenesis was also reported (Baskol et al, 2007;Lassouad et al, 2010).…”
Section: Environmental Factorsmentioning
confidence: 60%